PARI’S CHILDHOOD MEMORIES IN KHALED HOSSEINI’S AND THE MOUNTAINS ECHOED - FATIMAH (LITERA KULTURA : Journal of Literary and Cultural Studies, 2015)
Abstract Childhood memories have characteristics, have a link to a phenomenon called infantile amnesia, and can affect someone afterwards, particularly in adulthood. This study aims to describe Pari’s childhood memories depicted in And the Mountains Echoed novel and to reveal those childhood memories’ impact on Pari. As the tools for data analysis, firstly concept of memory will be delivered as a base to underlie childhood memories. The theory of childhood memories by Mark L. Howe and Patrick Estrade will be used to analyse the data. The data of the study is taken from author’s description and characters dialogue in And the Mountains Echoed novel which represent the childhood memories of Pari. The data is collected using library method and close reading technique. The analysis is presented using descriptive qualitative method. The result of analysis shows that Pari experiences infantile amnesia and her childhood memories are tend to be retained for a short period of time and rapidly decayed, are easily to be interfered, and can be categorized as autobiographical memories of child. At the beginning, childhood memories give negative impact on Pari. They brings her to a great confusion, it is because she is unable to recollect her own childhood memories. Finally, the childhood memories give positive impact on her, since she has seeked and found her big brother and her own roots by recollecting her childhood memories from another character. Keywords: childhood memories, infantile amnesia, early memory development.